Combination of the Parasitoid Spalangia endius Walker and Chemical Pesticides for the Control of Zeugodacus cucurbitae (Coquillett) - Lei Li; Dongyin Han; Jing Zhao; Haiyan Qiu; Fangping Zhang; Zhengpei Ye; Yueguan Fu (Insects, 2025)
Spalangia endius Walker, a pupal parasitoid of the alien invasive pest Zeugodacus cucurbitae (Coquillett), causes 33% host mortality. This study assessed whether combining S. endius with insecticides (abamectin, thiamethoxam, nitenpyram, emamectin benzoate, or beta-cypermethrin)—all effective against Z. cucurbitae—could enhance control efficacy. Among these, abamectin was the least toxic to adult S. endius. Surface contact treatments with 12 and 15 mg a.i./kg of abamectin did not significantly increase S. endius mortality. However, mixing 12 mg a.i./kg of abamectin into a honey solution to encourage ingestion decreased the survival, parasitism, and fecundity of S. endius. In olfactometer assays, S. endius adults avoided abamectin-treated host pupae, though prior exposure to abamectin mitigated this avoidance. The timing of abamectin soil application relative to host pupation and S. endius release affects host mortality. The most effective timing is spraying abamectin before host pupation (to expose Z. cucurbitae larvae) and then releasing S. endius. Field trials confirmed that combining abamectin (12 mg a.i./kg) with S. endius increased host mortality more than either treatment alone. In conclusion, abamectin (12 mg a.i./kg) is a suitable insecticide for combination with S. endius to control Z. cucurbitae. The application sequence should be spraying abamectin before hosts pupate and, only after that, releasing the parasitoid.